2016
DOI: 10.5539/ijbm.v12n1p178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prevailing HRM Practices on Job Satisfaction: A Comparative Study of Public and Private Higher Educational Institutions in India

Abstract: A sound HRM system can be generated through the effective HRM practices. HRM practices refer to all activities that are directed towards the management of human resources and the employment of the resources for fulfillment of desired organizational objectives. Job satisfaction "as summation of employees feelings in four important areas namely, job, management, personal adjustment and social relations". The present study was conducted on 526 faculty members randomly drawn of Government and Private affiliated hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Mostly, the employees are not satisfied with compensation package along with training and development, job design and responsibilities, management style, reward and motivation and career growth. Similarly, Qazi & Jeet (2017) in their study, based on a random sample using questionnaire of 526 faculty revealed that academic staffs of government educational institutes are satisfied with the overall HRM practices to a moderate extent. Higher level of satisfaction with training, teamwork and employee participation has been reported whereas, employees appeared less satisfied with performance appraisal and compensations.…”
Section: Introductionmentioning
confidence: 89%
“…Mostly, the employees are not satisfied with compensation package along with training and development, job design and responsibilities, management style, reward and motivation and career growth. Similarly, Qazi & Jeet (2017) in their study, based on a random sample using questionnaire of 526 faculty revealed that academic staffs of government educational institutes are satisfied with the overall HRM practices to a moderate extent. Higher level of satisfaction with training, teamwork and employee participation has been reported whereas, employees appeared less satisfied with performance appraisal and compensations.…”
Section: Introductionmentioning
confidence: 89%
“…Similarly, Bazana & Reddy, (2021) say that the recruitment processes and practices play the most important role in the organization. (Qazi & Jeet, 2016) obtained in their study, positive relation among recruitment and selection practices and employee satisfaction. Selection Practices: An worker choice is a very last selection technique in which any business enterprise attempt to pick out a proper character within side the proper manner to manipulate nicely skilled and certified HRs (Waheed & Yang, 2019).…”
Section: Review Of the Related Literaturementioning
confidence: 90%
“…We identified a correlation between errors 11 and 12 of the Performance Evaluation and Competencies (PEC) and Remuneration and Rewards (RR) factors, respectively, adding this correlation in the model to improve the fit, based on the theoretical support from the scientific literature. In this regard, the performance evaluation and the competencies must be conducted systematically, periodically, and impartially, revealing aspects that can enhance both the development and remuneration of employees [91]. Additionally, when performance evaluation has the character of subsidizing an effective plan for the development of competencies that affect the remuneration and reward system, instead of being merely punitive, there is a substantial improvement in the workers' commitment, satisfaction, and productivity [92].…”
Section: General Model and Measurement Models Testsmentioning
confidence: 99%